The efficacy and safety of Chinese herbal medicine as an add-on therapy for type 2 diabetes mellitus patients with carotid atherosclerosis: An updated meta-analysis of 27 randomized controlled trials - Zhang, Zehua; Leng, Yulin; Chen, Zhengtao; Fu, Xiaoxu; Liang, Qingzhi; Peng, Xi; Xie, Hongyan; Gao, Hong; Xie, Chunguang (Frontiers in Pharmacology, 2023)
Background: Type 2 diabetes mellitus (T2DM) is a clinical metabolic syndrome characterized by persistent hyperglycemia. Patients with T2DM are more likely to have carotid atherosclerosis (CAS), which can lead to dizziness, amaurosis or even stroke. Chinese herbal medicine (CHM) has shown possible efficacy and safety in treating T2DM patients with CAS. However, the existing evidence was not robust enough and the results were out of date. Objective: This meta-analysis aimed to summarize the current evidence and systematically evaluate the effects of CHM on carotid plaque, glucose and lipid metabolism and vascular endothelial parameters in T2DM patients with CAS, providing a reference for subsequent research and clinical practice. Methods: This study was registered in PROSPERO as CRD42022346274. Both Chinese and English databases were searched from their inceptions to 16 July 2022. All retrieved studies were screened according to inclusion and exclusion criteria. Randomized controlled trials (RCTs) using oral CHM to treat T2DM patients with CAS were included. The literature quality was assessed using the risk of bias assessment tool in the Cochrane Handbook. Data extraction was conducted on the selected studies. Review Manager 5.4 and Stata 16.0 were used for meta-analysis. Sources of heterogeneity were explored by meta-regression or subgroup analysis. Funnel plot and Egger’s test were used to assess publication bias and the evidence quality was assessed by Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results: 27 eligible studies, involving 2638 patients, were included in this study. Compared with western medicine (WM) alone, the addition of CHM was significantly better in improving carotid intima-media thickness (CIMT) [mean difference (MD) = -0.11mm, 95% confidence interval (CI): −0.15 to −0.07, p < 0.01], carotid plaque Crouse score [MD = −1.21, 95%CI: −1.35 to −1.07, p < 0.01], total cholesterol (TC) [MD = −0.34 mmol/L, 95%CI: −0.54 to −0.14, p < 0.01], triglyceride (TG) [MD = −0.26 mmol/L, 95%CI: −0.37 to −0.15, p < 0.01], low-density lipoprotein cholesterol (LDL-C) [MD = −0.36 mmol/L, 95%CI: −0.47 to −0.25, p < 0.01], high-density lipoprotein cholesterol (HDL-C) [MD = 0.22 mmol/L, 95%CI: 0.13 to 0.30, p < 0.01], glycated hemoglobin (HbA1c) [MD = −0.36%, 95%CI: −0.51 to −0.21, p < 0.01], fasting blood glucose (FBG) [MD = −0.33 mmol/L, 95%CI: −0.50 to −0.16, p < 0.01], 2-h postprandial glucose (2hPG) [MD = −0.52 mmol/L, 95%CI: −0.95 to −0.09, p < 0.01], homeostasis model assessment of insulin resistance (HOMA-IR) [standardized mean difference (SMD) = −0.88, 95%CI: −1.36 to −0.41, p < 0.01] and homeostasis model assessment of beta-cell function (HOMA-β) [MD = 0.80, 95%CI: 0.51 to 1.09, p < 0.01]. Due to the small number of included studies, it is unclear whether CHM has an improving effect on nitric oxide (NO), endothelin-1 (ET-1), peak systolic velocity (PSV) and resistance index (RI). No serious adverse events were observed. Conclusion: Based on this meta-analysis, we found that in the treatment of T2DM patients with CAS, combined with CHM may have more advantages than WM alone, which can further reduce CIMT and carotid plaque Crouse score, regulate glucose and lipid metabolism, improve insulin resistance and enhance islet β-cell function. Meanwhile, CHM is relatively safe. However, limited by the quality and heterogeneity of included studies, the efficacy and safety of CHM remain uncertain. More high-quality studies are still needed to provide more reliable evidence for the clinical application of CHM. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022346274